THE ROLE AND IMPORTANCE OF THE “NATIONAL ROAMING“ IN EMERGENCIES - Gligorijević, Milan M; Bošković, Milica; Maksimović, Aleksandar M (NBP. Nauka, bezbednost, policija, 2017)
After having analyzed recent catastrophic events that happened in the Republic of Serbia caused by flash flooding, at first glance, the struggle with floods seemed to be lost. Yet,  famous Serbian persistence or just a mere struggle for life of the citizens who showed extraordinary social solidarity in such difficult momentswere crucial once again. The unity was expressed in many ways, by providing assistance to the most vulnerable people in the evacuation of flooded areas, delivering basic foodstuffs and medical assistance, as well as in the field of telecommunications whose scope of work was very important but publicly invisible in such critical moments. Without such "key hub” that connected all relevant state factors into a whole providing them constancy and continuity in communications, everything would be pointless as “carrying coals to Newcastle”. This event, no matter how difficult and tedious, opened the subsequent analysis of many issues and spawned some great ideas. One of them is legally obliged introducing of "National roaming" at all telecommunications operators in our country, which will be later discussed in this paper.